Mental health consequences for adolescents during the Russian invasion of Ukraine: protocol for the Ukraine Adolescent Mental Health Study - Osokina, Olga; Silwal, Sanju; Westerlund, Minja; Heinonen, Emmi; Hinkka-Yli-Salomäki, Susanna; Putyatin, Gennadiy; Yaschchyshyna, Yuliia; Skokauskas, Norbert; Hodes, Matthew; Sourander, Andre (Frontiers in Child and Adolescent Psychiatry, 2025)
BackgroundIn February 2022, Russia launched a full scale-invasion of Ukraine, which is the largest European ground offensive since the Second World War. However, the Russian-Ukrainian war began in 2014, when Russia invaded and annexed the Crimea peninsula and occupied part of the eastern regions of Ukraine. This prolonged exposure to war, with its many casualties and massive displacement, has negatively affected the mental health of adolescents, although a comparison of the impacts on adolescents exposed to the various stages of war has not been documented. Our aim is to explore the effects of differential wartime traumatic stressor exposure and displacement on the mental health of adolescents exposed to the Russian invasion in Ukraine since 2014.MethodsThe Ukraine Adolescent Mental Health Study (UAMS) is a time-trend study comprising two cross-sectional school surveys. The first survey was carried out in 2016–2017, two years after eastern Ukraine was invaded by Russia. The second survey was conducted after the 2022 full-scale Russian invasion. Both surveys used the same method and included participants aged 11–17 years from two areas in Ukraine, the Donetsk region and the Kirovograd region. In 2016–2017, we focused on adolescents living in the eastern Donetsk region who had been exposed to war since 2014 and those living in the central Kirovograd region, which was not directly affected by the invasion. The new survey will enable us to compare exposure to traumatic wartime stressors and mental health problems among adolescents over time and between the two regions. Several standardized tools will be used to assess post-traumatic stress disorder, depression, anxiety, suicidal ideation, suicide attempts and self-harm behavior.DiscussionThis study will provide a unique opportunity to examine the escalating psychological consequences of the ongoing war on adolescents in Ukraine. Such information is crucial for understanding adolescents’ mental health needs, and thus for providing psychosocial support and developing mental health interventions.